Pengembangan Perangkat Pembelajaran Melalui In House Training Model Jigsaw untuk Meningkatkan Kemampuan Paedagogi Guru SDN Subah 01 Batang - Jaka, Jaka; Dwijayanti, Ida; Rasiman, Rasiman (Pena Edukasia, 2022)
The problems in this study are (1) How to develop valid syllabus, lesson plans, materials and LKPD, (2) Can teachers' pedagogical competence be improved by In House Training Jigsaw Model? (3) Are there any differences in the tools developed by the teacher before participating in the In House Jigsaw Model Training and after? (4) What is the teacher's perception of the influence of the Jigsaw Model In House Training on the device development ability? The aims of this research are; (1) Developing the teacher's ability to develop valid learning tools, (2) Improving the pedagogical competence of teachers through In House Training Model Jigsaw, (3) Knowing the differences in tools developed by teachers before participating in In House Training Model Jigsaw and after, (4) The teacher has the correct perception of the development of learning tools after participating in the In House Training Model jigsaw. The population in this study were SD Subah 01 teachers consisting of 12 class teachers and subject teachers. The data collection method used is the questionnaire method. Data analysis used descriptive analysis, standardization test and hypothesis testing which included validity analysis to analyze the validity of the learning device product and t test to analyze the ability to construct learning tools before and after IHT. Data analysis using SPSS 1.6 application. From the results of the research it can be seen that the development of learning tools from the validation results of the three experts obtained an average of 70.33 with a Very Good predicate; -6.996, and sig (2-tailed) of 0.000. Based on the output table "Paired Samples Test" it is known that the value of Sig. (2-tailed) of 0.000 <0.05, as the basis for making a decision on the Paired Samples Test, it can be concluded that Ho is rejected. Thus it can be concluded that the ability to prepare lesson plans before IHT is not the same as the ability to prepare lesson plans after IHT (meaning that the implementation of IHT affects the ability to prepare lesson plans for teachers). The results of preparing lesson plans before IHT (?????= 63.17) and the ability to prepare lesson plans after IHT (?????= 84.50). Furthermore, from the output table it is also known that t-count = 6.996. Teachers have a good perception of the effect of In House Training Jigsaw Model on the ability to develop learning tools. The mean (average) of combining before and after IHT is -32250, the t-count value is -7.821, and sig (2-tailed) is 0.000. Based on the output table "Paired Samples Test" it is known that the value of Sig. (2-tailed) of 0.000 <0.05, then as the basis for making decisions on the Paired Samples Test, it can be concluded that Ho is rejected. Thus, it can be concluded that the perception of the correct development of tools before IHT is not the same as the perception of development of tools after IHT (meaning that the implementation of IHT affects the perception of the development of tools for teachers). Perception of learning device development before IHT (?????= 53.80) and Ability to compose lesson plans after IHT (?????= 85.75). Furthermore, from the output table above, it is also known that t-count = 17.821.